Clinical benefit of atrio-ventricular delay optimization in patients with a dual-chamber pacemaker: a pilot study. The CBRAVO trial (NCT01998256). Issue 3 (1st June 2016) - Cools, Thijs; Daerden, Tara; Herbots, Lieven; Geukens, Robert; Koopman, Pieter; Dilling-Boer, Dagmara; Hansen, Dominique; Vranckx, Pascal; Dendale, Paul
Abstract : Objective Outcome data on exercise capacity following atrio-ventricular (AV) optimization of dual-chamber pacing are sparse. Pacemaker settings are often left at manufacturers' nominal values upon implantation. We studied the short-term effect of AV optimization on exercise capacity in patients with a dual-chamber pacemaker. Methods and results Twenty-eight patients (mean age 73 ± 14 y) with a dual-chamber pacemaker, were randomized towards either nominal AV settings (group 1) or echo-guided AV optimization using the iterative mitral inflow VTI (velocity time integral) method (group 2) at baseline. At 4 weeks, patients were crossed-over to AV optimization in group 1 and returned to nominal AV settings in group 2 for another period of 4 weeks. Oxygen uptake efficiency slope improved significantly after AV optimization (by 126.7 mL/logL ± 190.7 mL/logL; P = 0.003). Conclusions AV optimization in dual-chamber pacing significantly improved functional capacity after 4 weeks. These data provide the background for further validation studies.